Plan estratégico de marketing para la empresa Lavatec Lc del cantón Calvas, provincia de Loja periodo 2022. - Montenegro Calva, Luis Adrián (2023)
The present research work aims to carry out a "Strategic marketing plan for Lavatec Lc Washing and Lubricating Company", which will allow the design of helpfull strategies to promote the growth of the company and to obtain greater economic profitability, subsequently theoretical content related to the subject under study were reviewed. Likewise, the present work has the appropriate methodology which has allowed to obtained the necessary results to establish the strategies to strengthen the image and improve customer loyalty, it is worth mentioning that the research is of a mixed nature, it is based on three specific objectives, first, a situational diagnosis of the company was carried out, an internal and external analysis of the company was made to determine the most appropriate marketing strategies. In the internal analysis the EFI matrix was made with data obtained through surveys, interviews and through direct observation that was made to the company, yielded a result of 2.52 which indicates that the strengths outweigh the weaknesses; In the external analysis, the EFE matrix was carried out taking into account factors such as political, economic, social, technological and environmental factors, resulting in a score of 2. The SWOT matrix was used to determine the strategic objectives and develop a strategic marketing plan to promote the company through the local media. Finally, the conclusions and recommendations were made. Keywords: Company positioning, Customer loyalty, Marketing strategies.